Analisis Pengendalian Kualitas Cacat dengan Metode Six Sigma pada Perusahaan Percetakan (Studi Kasus: PT. Delta Mandiri) - Willy Oktavianus; Dino Caesaron (Universitas Bunda Mulia, 2017)
The globalization era is forcing companies to improve the quality of their products. Quality is an important thing to be a good and competitive company. This research is using Six Sigma and using Define-Measure-Analyze-Improve-Control (DMAIC) as a concept. Some of the statistical tools are used in this study such as the Check Sheet, Histogram, Pareto, and Fishbone. Based on the Check Sheet and the calculation showed the types of defects such as not suitable spot, bubble, not evenly, and there is absorption that has shown the sigma level is 4.45 and Process Capability (Cp) is 99.30%. Each type of defect has analyzed by using Pareto with a ratio of 80:20, and acquired defects: not suitable spot 46.4%, bubble 35.2%, not evenly 16.8% and other defects 1.7%. Furthermore, the defects will be analyzed using Fishbone based on man, machine, method, and material as the analyzing factors. Fishbone shows that there are several factors which creating defects. The improvement does by the suggestions for improvements and by using the Solution Tree.Keywords: Six Sigma, DMAIC, Statistical Process, Capability Process.